Effect of different mitigation options on growth, productivity and economics of wheat (Triticum aestivum) - KUMAR, O; JAIN, N; SINGH, K; RAMAWAT, N; BHATIA, A; SHARMA, D K (The Indian Journal of Agricultural Sciences, 2020)
Wheat (Triticum aestivum L.) is second most important food grain after rice and is consumed in different forms. The production of wheat in India is currently facing new challenges due to increasing population and adverse impacts of climate change. The production of wheat has increased significantly after the introduction of high yielding varieties. Modern wheat cultivars require adequate amount of nitrogen (N) fertilizer and several irrigations for economical production. The amount and type of nitrogen fertilizers not only affect the production of wheat but also has impact on climate change due to emission of nitrous oxide. A field experiment was conducted in 2016-17 to study the impact of water management (3 and 5 irrigations) and nitrogen fertilizer (urea, neem coated urea (NCU), urea with thiourea, and leaf colour chart (LCC) based N application) on wheat production and profitability. The nitrogen-management practices and irrigation practices significantly influenced the yield parameters, cost of cultivation, net returns and benefit to cost ratio of wheat crop. Grain yield was increased by 15.89% (p ≥ 0.05) in 5 irrigations compared to 3 irrigations. The grain yield increased by 3.0%, 3.4% and 5.9% in treatments where N was applied using NCU, LCC based N application and urea + thiourea respectively, over urea treatment. Grain yield per kg of N applied was highest in LCC based N application treatment followed by thiourea + urea, NCU and urea N treatments. Highest gross returns was from thiourea treatment however the net returns and B: C ratio were highest in LCC based urea N application due to higher biological yield and saving of 20 kg nitrogen per ha. The study revealed that the economic performance of greenhouse gas mitigation technologies where N was applied based on the plant requirement using leaf colour chart and 5 irrigations was the best followed by application of nitrification inhibitor thiourea with urea and 5 irrigations.